Pertanggungjawaban Pidana terhadap Penganiayaan yang Dilakukan Anak kepada Orang Tua Ditinjau dalam Perspektif HAM - I Wayan Ogi Wiryawan; I Made Minggu Widyantara; Luh Putu Suryani (Jurnal Preferensi Hukum, 2021)
At present, abuse of parents by children, often occurs in the community which is commonly referred to as child abuse against parents. Children become cruel due to two factors, namely internal factors and external factors so that they are desperate to commit inhumane behavior towards their own parents. This case is also a violation of human rights that must be enforced. However, a child cannot be convicted of being underage. This study aims to analyze the criminal arrangements for minors who commit crimes against parents and explain the criminal sanctions given to a child who commits a criminal act of molestation. The research method used is normative legal research using a statutory approach as well as a conceptual approach. The data used are primary data, namely legal rules that are sorted systematically consisting of legislation, while secondary data consists of books, texts, principles and writings on laws related to persecution. There is also a form of writing in this research. The results of this study indicate that children can still be subject to criminal sanctions but can also be subject to sanctions in the form of fostering sanctions by related agencies. The child in this case who commits the crime of abuse is a minor, the punishment is different from ordinary punishment where child punishment is aimed at fostering the child and not focusing on the deterrent effect of the criminal.